2023
DOI: 10.1038/s41467-023-35939-w
|View full text |Cite
|
Sign up to set email alerts
|

Projected health impact of post-discharge malaria chemoprevention among children with severe malarial anaemia in Africa

Abstract: Children recovering from severe malarial anaemia (SMA) remain at high risk of readmission and death after discharge from hospital. However, a recent trial found that post-discharge malaria chemoprevention (PDMC) with dihydroartemisinin-piperaquine reduces this risk. We developed a mathematical model describing the daily incidence of uncomplicated and severe malaria requiring readmission among 0–5-year old children after hospitalised SMA. We fitted the model to a multicentre clinical PDMC trial using Bayesian m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Measures for 5–18 year age group identified in the study have been proven successful [ 32 34 ]. Furthermore, Tiono et al .…”
Section: Discussionmentioning
confidence: 99%
“…Measures for 5–18 year age group identified in the study have been proven successful [ 32 34 ]. Furthermore, Tiono et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the studies were powered to address this, the fraction of the population targeted by post-discharge malaria chemoprevention and the corresponding selective drug pressure on the parasite population is much smaller than with seasonal malaria chemoprevention, IPT in pregnancy, perennial malaria chemoprevention (previously IPT in infants), or IPT in schoolchildren, which each include all members of a target population regardless of health status. 35 …”
Section: Discussionmentioning
confidence: 99%
“…7 A mathematical model of the projected impact of post-discharge malaria chemoprevention across malaria-endemic African countries suggested that if all hospitalised children aged 0–5 years with severe anaemia were given post-discharge malaria chemoprevention in these areas, 38 600 readmissions (range 16 900–88 400) and 2176 deaths (1078–4315) could be prevented annually. 35 The impact would be greatest in countries with higher transmission intensities. In areas with a P falciparum prevalence greater than 10% in children aged 2–10 years, an estimated 4·8 children would need to be given post-discharge malaria chemoprevention to prevent one readmission, and 112 children to prevent one death, consistent with the findings in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trials used three alternative drug regimens—monthly sulfadoxine-pyrimethamine (SP) until the end of the malaria transmission season (average: 3.1 doses per child) (N = 1200, the Gambia [ 3 ]), monthly artemether-lumefantrine (AL) given at 4 and 8 weeks post-discharge (N = 1414, Malawi [ 4 ]), or monthly dihydroartemisinin-piperaquine (DP) given at the end of the 2nd, 6th, and 10th-week post-discharge (N = 1049, Uganda and Kenya [ 5 ]). Evidence from additional studies on acceptability [ 6 ], delivery strategies [ 7 ], cost-effectiveness [ 8 ], and modelling [ 9 ] were also reviewed. The WHO recommendation stopped short of recommending which anti-malarial drug should be used and how best to deliver PDMC, indicating that these decisions should be made at the national level and adapted to suit local contexts.…”
Section: Introductionmentioning
confidence: 99%